Aplikasi Pembelajaran Konsep Ekologi Menggunakan Augmented Reality Pada Android - Andryanto. A, Erwin Gatot Amiruddin, Andi Anan Saputra Habum, Akbar Iskandar (Celebes Computer Science Journal, 2021)
This study aims to design an interactive, effective and efficient ecological learning application; implementation of the Waterfall method in system development. This data was obtained through (1) Field Research, (2) Literature Study (3) Questionnaire. Using C# programming scripts. The results of this study are an application for learning the concept of ecology with Augmented Reality technology that can run on devices whose operating system is Android 6.0 (marshmallow) to Android 10. This application contains subject matter such as understanding ecology, understanding and components of ecosystems, units of living things, interactions between living things, energy flows, symptoms and impacts of ecological crises, and finally, biogeochemical cycles. The percentage of question results yielded 220%.